Evaluation of the Scottish Patient Safety Fellowship programme 2008–2013. (March 2015) - O'Connor, Patricia; Fearfull, Anne
Building improvement capacity and capability skills that enable staff to keep patients safe and improve care is essential to today's health care environments. The Scottish Patient Safety Fellowship is an educational programme designed to build clinical leadership skills to build, improve and enhance patient care and the patient experience. The Scottish Patient Safety Fellowship is unique as it is an embedded component of the National Health Service Education for Scotland's (NES) capacity and capability plan for clinicians to be leading health care improvement. This research evaluation used mixed methods to examine the experience of the fellows in Cohorts 1–5 (2008–2013) ( n = 76), alongside the view of the fellows' organisational sponsors – the chief executive officers ( n = 12) and the senior leaders ( n = 9) of the Scottish Patient Safety Fellowship Programme. This research was supported by Healthcare Improvement Scotland (HIS) and NHS Education for Scotland.